2019
DOI: 10.1002/asl.939
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term trends in tropical cyclone tracks around Korea and Japan in late summer and early fall

Abstract: This study investigates long-term trends in tropical cyclones (TCs) over the extratropical western North Pacific (WNP) over a period of 35 years .The area analyzed extended across 30-45 N and 120-150 E, including the regions of Korea and Japan that were seriously affected by TCs. The northward migration of TCs over the WNP to the mid-latitudes showed a sharp increase in early fall. In addition, the duration of TCs over the WNP that migrated northwards showed an increase, specifically in early to mid-September.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
(36 reference statements)
1
18
0
Order By: Relevance
“…SST in the WNP has increased more significantly in the mid‐latitudes than other regions in recent decades (Deser et al., 2010; Lee, Cha, et al., 2019) while being projected to substantially increase around the Korean Peninsula and Japan in future climate scenarios (Lee, Jin, et al., 2019; Murakami et al., 2011; Tsou et al., 2016). This warming pattern is similar to the negative PDO phase.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…SST in the WNP has increased more significantly in the mid‐latitudes than other regions in recent decades (Deser et al., 2010; Lee, Cha, et al., 2019) while being projected to substantially increase around the Korean Peninsula and Japan in future climate scenarios (Lee, Jin, et al., 2019; Murakami et al., 2011; Tsou et al., 2016). This warming pattern is similar to the negative PDO phase.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…As shown in Figure 5, such wind pulses are largely associated with the extratropical cyclones over the East Asia. Previous studies have revealed that the intensity, frequency, and path of the extratropical cyclones over the East Asia were influenced by large‐scale climatic patterns, such as the global warming and Pacific decadal oscillation (Chen et al., 2019; M. Lee et al., 2019; J. Lee et al., 2020). One may, therefore, expect the causal link between the large‐scale climatic pattern and thermocline mixing.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that the intensity, frequency, and path of the extratropical cyclones over the East Asia were influenced by large-scale climatic patterns, such as the global warming and Pacific decadal oscillation (Chen et al, 2019;M. Lee et al, 2019;J.…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce forecast error, there has been a lot of effort to improve forecast models related to physical processes, convection, ocean feedback and resolution (Islam et al, 2015;Park et al, 2008;Soden and Held, 2006;Kendon et al, 2012). Also, the performance of the forecast models has been improved by techniques related to initial condition (Kwon and Cheong, 2010;Cha et al, 2013), forcing data (Kang et al, 2005;Moon et al, 2019) and model output (Piani et al, 2010;Dosio and Paruolo, 2011).…”
Section: Introductionmentioning
confidence: 99%